ISU TERKINI DALAM PEMBELAJARAN SASTRA: KELIMPAHAN INFORMASI, KECERDASAN BUATAN, DAN LITERASI DIGITAL - Dipa Nugraha; Main Sufanti (Universitas Muhammadiyah Surakarta, 2023)
Chairil Anwar's poems have been discussed by dozens of Indonesian literary critics and academics. Even so, there could still be cases of incorrect identification of Chairil Anwar's poetry by Indonesian literary academics. This article is an investigative research article. Data was obtained from surveys through cyberspace using the Google search engine with certain keywords and applying snowballing techniques. In order to enrich the data in explaining cases of incorrect identification of Chairil Anwar's poetry, class simulations were carried out. The first class simulation resulted in findings of the phenomenon of information overload as the cause of the identification of Chairil Anwar's poetry. In another class simulation, it was found that artificial intelligence in open-access conversation formats such as the GPT Chat which was just present at the time this article was written needs to be closely observed for its development and potential in literary learning. The conclusion of this article is that there is an urgency to increase Indonesian literary literacy in literary learning in tertiary institutions as well as the need for its integration with digital literacy learning.Keywords: Literary Myopia, Digital Literacy, Information Overload, Artificial Intelligence, ChatGPT